1998
DOI: 10.1016/s0010-0277(98)00043-2
|View full text |Cite
|
Sign up to set email alerts
|

Music and emotion: perceptual determinants, immediacy, and isolation after brain damage

Abstract: This study grew out of the observation of a remarkable sparing of emotional responses to music in the context of severe deficits in music processing after brain damage in a nonmusician. Six experiments were designed to explore the perceptual basis of emotional judgments in music. In each experiment, the same set of 32 excerpts taken from the classical repertoire and intended to convey a happy or sad tone were presented under various transformations and with different task demands. In Expts. 1 to 3, subjects we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

31
369
3
22

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 413 publications
(440 citation statements)
references
References 34 publications
31
369
3
22
Order By: Relevance
“…Like in facial expressions and in speech prosody, basic emotions can be universally recognized in music (Balkwill & Thompson, 1999;Fritz et al, 2009) and recognition can occur within less than a second (Peretz, Gagnon, & Bouchard, 1998). The identification of emotions in music is highly consistent across subjects (Bigand, Vieillard, Madurell, Marozeau, & Dacquet, 2005;Thompson, 2009) and it has been shown to correlate with emotional intelligence (Resnicow, Salovey, & Repp, 2004).…”
Section: Emotion Recognition In Music Changes Across the Adult Life Spanmentioning
confidence: 99%
“…Like in facial expressions and in speech prosody, basic emotions can be universally recognized in music (Balkwill & Thompson, 1999;Fritz et al, 2009) and recognition can occur within less than a second (Peretz, Gagnon, & Bouchard, 1998). The identification of emotions in music is highly consistent across subjects (Bigand, Vieillard, Madurell, Marozeau, & Dacquet, 2005;Thompson, 2009) and it has been shown to correlate with emotional intelligence (Resnicow, Salovey, & Repp, 2004).…”
Section: Emotion Recognition In Music Changes Across the Adult Life Spanmentioning
confidence: 99%
“…Further compelling evidence of implicit musical effects comes from studies of brain-damaged patients suggesting that cortical processing may not be essential for music to arouse emotions (Panksepp & Bernatzky, 2002;Peretz et al, 1998). A patient with a large lesion of the temporal and frontal cortices had severe impairments in music perception but intact capacity for music appreciation (Peretz et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…A patient with a large lesion of the temporal and frontal cortices had severe impairments in music perception but intact capacity for music appreciation (Peretz et al, 1998). A number of evolutionarily old brain regions, such as the amygdala, insula, and striatum, have consistently been implicated in music emotion induction and enjoyment (Blood & Zatorre, 2001;Blood et al, 1999;Brattico et al, 2013;Koelsch, 2014;Koelsch et al, 2006;Salimpoor et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Psychological studies have shown that emotions conveyed by music are objective enough to be valid for mathematical modeling [4,13,24,32]. Moreover, Vieillard et al [43] demonstrated that within the same culture, the emotional responses to music could be highly consistent.…”
Section: Introductionmentioning
confidence: 99%